Direct conversion of glyceride-based oil into renewable jet fuels. (October 2020) - Lin, Cheng-Han; Wang, Wei-Cheng
Abstract: Hydro-conversion of triglyceride to renewable jet fuel (HRJ) plays an important role in drop-in aviation fuels and has drawn the attention of scholars because of its potential to reduce aircraft pollution and mitigate greenhouse gas emissions. A direct one-step conversion of glyceride-based oil into HRJ over NiAg supported on SAPO-11 zeolite was investigated in this paper. Also, the properties of the catalysts were characterized using XRD, TEM, N2 adsorption-desorption, TG and Py-FTIR. The NiAg/SAPO-11 catalyst showed good performance in terms of hydro-processing, hydro-cracking, and hydro-isomerization reactions with the assistance of citric acid (CA) and phosphotungstic acid hydrate (HPW). The key to high conversion, high selectivity, and high iso-alkane content depended mostly on the reaction temperature, metal dispersion, acid content and the pore structures of the zeolite. Furthermore, the fuel properties were tested in a GC-MS/FID and flash point tester to ensure to meet the ASTM D7655 specifications. Under the optimal reaction conditions, a conversion of 100%, selectivity of 84%, an I-to-N ratio of 2.1, a yield of 72%, an aromatics content of 7%, and a flash point of 58 °C were obtained. The mass, carbon and energy yield for both one-step and two-step processes were also determined. This study provides a novel technique for producing renewable jet fuel with higher production yield. Graphical abstract: Image 1 Highlights: One-step conversion of glyceride-based oil into HRJ over NiAg/SAPO-11 was studied. Under the optimal conditions, a 100% conversion and 84% selectivity were obtained. An 2.1 I-to-N ratio, 72% yield and 7% aromatics content were obtained.